2012
DOI: 10.1029/2010gb003956
|View full text |Cite
|
Sign up to set email alerts
|

The sequestration sink of soot black carbon in the Northern European Shelf sediments

Abstract: To test the hypothesis that ocean margin sediments are a key final repository in the large‐scale biogeospheric cycling of soot black carbon (soot‐BC), an extensive survey was conducted along the ∼2,000 km stretch of the Swedish Continental Shelf (SCS). The soot‐BC content in the 120 spatially distributed SCS sediments was 0.180.130.26% dw (median with interquartile ranges), corresponding to ∼5% of total organic carbon. Using side‐scan sonar constraints to estimate the areal fraction of postglacial clay sedimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 86 publications
3
58
1
Order By: Relevance
“…IV (0.02570.001 mg/cm 2 /yr), and were similar to those reported for deep-sea sediments (0.0005-0.0078 mg/cm 2 /yr) (Lohmann et al, 2009). The BC burial flux was 0.19270.102 mg/cm 2 /yr, 0.21970.249 mg/cm 2 /yr, and 0.11570.103 mg/cm 2 /yr for Regs II, III, and V, respectively, which was within the range of results reported for other continental shelf regimes worldwide (0.002-0.3 mg/cm 2 /yr) (Sánchez-García et al, 2012). Overall, the extensive coverage of this study allowed us to develop a comprehensive understanding of BC cycling in marine sediments.…”
Section: Inventories Of Bc In the East China Seasupporting
confidence: 78%
See 1 more Smart Citation
“…IV (0.02570.001 mg/cm 2 /yr), and were similar to those reported for deep-sea sediments (0.0005-0.0078 mg/cm 2 /yr) (Lohmann et al, 2009). The BC burial flux was 0.19270.102 mg/cm 2 /yr, 0.21970.249 mg/cm 2 /yr, and 0.11570.103 mg/cm 2 /yr for Regs II, III, and V, respectively, which was within the range of results reported for other continental shelf regimes worldwide (0.002-0.3 mg/cm 2 /yr) (Sánchez-García et al, 2012). Overall, the extensive coverage of this study allowed us to develop a comprehensive understanding of BC cycling in marine sediments.…”
Section: Inventories Of Bc In the East China Seasupporting
confidence: 78%
“…However, data is sparse regarding regional BC fluxes, as previous investigations have focused on only a few key regions, including the New England continental shelf (0.4-0.8 Â 10 6 t/yr) (Gustafsson and Gschwend, 1998), the South Atlantic shelves and basin (0.48-0.7 Â 10 6 t/yr) (Lohmann et al, 2009), and the Northern European Shelf (1.1 Â 10 6 t/yr) (Sánchez-García et al, 2012). Thus, an inventory and assessment of the burial flux of BC in marginal sea sediments is essential for gaining a better understanding of the regional carbon cycle and its links to global change.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the upper Gulf, the other two higher BC burial fluxes (>300 mg/cm 2 /y) were concurrent within the finer deposits in the lower Gulf, indicating a potential depository for the land-based exported BC. The estimated BC burial fluxes in this study were comparable with those of the coastal regimes around the world (Table 1), such as the Gulf of Cadiz (120 mg/cm 2 /y) and the Gulf of Maine (131 mg/cm 2 /y) (Gustafsson and Gschwend, 1998;Sanchez-García et al, 2013), but they were lower than those areas with strong human impact, such as the Swedish Continental Shelf (1103 mg/cm 2 /y) (Sanchez-García et al, 2012). In contrast, this result was still 2e4 orders higher than those from the pelagic and deep sea sediment due to the relatively lower sedimentation rates, such as the Pacific deep sea (0.01e0.1 mg/cm 2 /y) (Smith et al, 1973) and the South Atlantic Ocean (2.27 mg/cm 2 /y) (Lohmann et al, 2009).…”
Section: Mass Inventory Of Bc In the Got Sediments And Its Comparisonmentioning
confidence: 47%
“…Therefore, the extensive study of the BC occurrence and mass inventory in the continental margins is essential for a better understanding of the global biogeochemical cycle of BC. However, a vast majority of the existing studies on the sedimentary BC in the coastal margins were geographically within high-latitude regions (e.g., Europe and America), such as the Northern European shelf (Sanchez-García et al, 2012), the Gulf of Cadiz (Sanchez-García et al, 2013), the Gulf of Maine (Gustafsson and Gschwend, 1998;Flores-Cervantes et al, 2009), the pan-arctic estuaries (Guo et al, 2004;Elmquist et al, 2008); the Washington coast (Dickens et al, 2004), etc., however, only little attention has been paid to the continental shelf of Asia (e.g., Wang and Li, 2007;Sun et al, 2008), particularly for the Southeast Asia (SE Asia), a tropical region, which has been identified as a major BC emission source region due to frequent forest fires, biomass burning and escalating fossil fuel utilisation (Streets et al, 2003). Moreover, the tropical coastal margins in SE Asia also serve as an important source emission region for coastal BC export due to the inherent nature of rapid transferring of land-based materials into the aquatic system via strong rain and surface runoff (Nittrouer et al, 1995;Zakaria et al, 2002;Saha et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported BC deposition rates for different environmental types of environmental media. Sánchez-García et al (2012) found that the soot deposition rate reached 1 g m -2 yr -1 for recent European shelf sediments, and more recently, Lehndorff et al (2015) reported that from 1958-1971 the input of industrial BC deposition to arable soils from Halle, Germany was 9 g m -2 yr -1 . Tang et al (2013) observed that the mean deposition of BC for atmospheric dustfall in Beijing was 1.20 g m -2 yr -1 .…”
Section: Bc Deposition and Environmental Implicationsmentioning
confidence: 99%